PEDAGOGICAL INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGY AMONG TEACHER EDUCATORS IN CENTRAL VISAYAS, PHILIPPINES - Marcial, Dave E. (Silliman Journal, 2022)
Information and communication technology (ICT) changes the way education is delivered. ICT highly supports student-centered environment. This paper examines the level of pedagogical integration of ICT among teacher educators in Central Visayas, Philippines. The study used a survey questionnaire based on the National ICT Competency Standard for Teachers. A total of 383 responses from 76 private and public higher education institutions were included in the analysis using weighted mean and chi square. The study reveals that the level of pedagogical integration of ICT among the teacher educators is moderate. The result implies that the teacher educators are familiar with the pedagogical operations of ICT but have not experienced the actual implementation of it. The level of competency in the pedagogical integration of ICT is affected by age, status, institution, and number of years in teaching. Teacher educators from private higher education institutions (HEIs) have a higher competency level than those who are affiliated from public HEIs. Those who have a desktop, Smartphone and a laptop computer with Internet accessibility have a higher competency